Intranasal delivery of targeted polyfunctional gold–iron oxide nanoparticles loaded with therapeutic microRNAs for combined theranostic multimodality imaging and presensitization of glioblastoma to temozolomide. (October 2019) - Sukumar, Uday K.; Bose, Rajendran J.C.; Malhotra, Meenakshi; Babikir, Husam A.; Afjei, Rayhaneh; Robinson, Elise; Zeng, Yitian; Chang, Edwin; Habte, Frezghi; Sinclair, Robert; Gambhir, Sanjiv S.; Massoud, Tarik F.; et al.
Abstract: The prognosis for glioblastoma (GBM) remains depressingly low. The biological barriers of the brain present a major challenge to achieving adequate drug concentrations for GBM therapy. To address this, we explore the potential of the nose-to-brain direct transport pathway to bypass the blood-brain barrier, and to enable targeted delivery of theranostic polyfunctional gold-iron oxide nanoparticles (polyGIONs) surface loaded with therapeutic miRNAs (miR-100 and antimiR-21) to GBMs in mice. These nanoformulations would thus allow presensitization of GBM cells to the systemically delivered chemotherapy drug temozolomide (TMZ), as well as in vivo multimodality molecular and anatomic imaging of nanoparticle delivery, trafficking, and treatment effects. First, we synthesized GIONs coated with β-cyclodextrin-chitosan (CD-CS) hybrid polymer, and co-loaded with miR-100 and antimiR-21. Then we decorated their surface with PEG-T7 peptide using CD-adamantane host-guest chemistry. The resultant polyGIONs showed efficient miRNA loading with enhanced serum stability. We characterized them for particle size, PDI, polymer functionalization, charge and release using dynamic light scattering analysis, TEM and qRT-PCR. For in vivo intranasal delivery, we used U87-MG GBM cell-derived orthotopic xenograft models in mice. Intranasal delivery resulted in efficient accumulation of Cy5-miRNAs in mice treated with T7-targeted polyGIONs, as demonstrated by in vivo optical fluorescence and MR imaging. We measured the therapeutic response of these FLUC-EGFP labelled U87-MG GBMs using bioluminescence imaging. Overall, there was a significant increase in survival of mice co-treated with T7-polyGIONs loaded with miR-100/antimiR-21 plus systemic TMZ, compared to the untreated control group, or the animals receiving non-targeted polyGIONs-miR-100/antimiR-21, or TMZ alone. Once translated clinically, this novel theranostic nanoformulation and its associated intranasal delivery strategy will have a strong potential to potentiate the effects of TMZ treatment in GBM patients.